Cross-Border Regulatory Coordination and Industrial Chain Resilience: Practices of Institutional Opening-Up in the Belt and Road Initiative and Regional Economic Integration - Zhi Pang (International Journal of Social Sciences and Public Administration, 2026)
In the context of the restructuring of global industrial chains and the deepening of regional economic and trade cooperation, the regulatory rules of countries along the Belt and Road Initiative (BRI) are incompatible, and institutional barriers are high, which directly affect the stable operation of regional industrial chains. In order to strengthen the resilience of the industrial chain, promote institutional opening-up and regional economic integration, this article relies on the cooperation practices of regulatory coordination between China and BRI participating countries, and combines statistical data released by the Ministry of Commerce and the General Administration of Customs to analyze the intrinsic linkage between cross-border regulatory coordination and industrial chain resilience. The article reviewed practical innovations such as the China-ASEAN Free Trade Area (CAFTA) 3.0, the Shanghai Cooperation Organization's trade facilitation mechanism, and the international trade "single window", and found that there are still shortcomings in the region, such as significant differences in regulatory rules, inadequate implementation of collaborative mechanisms, and uneven digital regulatory capabilities. Research shows that promoting cross-border regulatory coordination and deepening institutional opening-up can effectively reduce cross-border transaction costs, enhance supply chain resilience to external risks, and provide institutional references for the high-quality development of the BRI and regional economic integration.